Weyl points in photonic-crystal superlattices. (19th August 2015) - Bravo-Abad, Jorge; Lu, Ling; Fu, Liang; Buljan, Hrvoje; Soljačić, Marin
Abstract: We show that Weyl points can be realized in all-dielectric superlattices based on three-dimensional (3D) layered photonic crystals. Our approach is based on creating an inversion-breaking array of weakly-coupled planar defects embedded in a periodic layered structure with a large omnidirectional photonic band gap. Using detailed band structure calculations and tight-binding theory arguments, we demonstrate that this class of layered systems can be tailored to display 3D linear point degeneracies between two photonic bands, without breaking time-reversal symmetry and using a configuration that is readily-accessible experimentally. These results open new prospects for the observation of Weyl points in the near-infrared and optical regimes and for the application of Weyl-physics in integrated photonic devices.